Literature Review: The Potential of Escherichia coli Bacteria As Insulin Producer - Risah, Risah; Primayanti, Tiara (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2026)
Diabetes mellitus is a chronic metabolic disease that requires the use of insulin as the main treatment, especially in people with type 1 diabetes and some cases of type 2 diabetes. Insulin plays an important role in regulating blood glucose levels by increasing glucose absorption by peripheral tissues and inhibiting glucose production by the liver. With the increasing need for insulin globally, recombinant insulin production technology using Escherichia coli bacteria has become an efficient, safe and economical alternative. This research is a literature review aimed at exploring the potential of E. coli as an expression system in the production of recombinant insulin. Based on the results of a review of several literatures, E. coli has several advantages such as fast growth, ease of genetic manipulation and the ability to produce insulin in large quantities with high quality. The application of genetic engineering technologies, plasmid systems, and protein expression has enabled the production of insulin that is purer and reduces immunological side effects compared to animal insulin. Thus, E. coli is a very potential and relevant platform in the development of recombinant insulin to meet global diabetes treatment needs.